Literasi bahasa di rumah: Pemahaman orang tua terhadap keterlambatan berbicara anak - Hasanah, Nor Izatil; Faziah, Nurul (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2025)
Speech delay in early childhood is an increasingly common developmental problem that impacts on children's communication, social and learning skills. This study aims to explain parents' understanding of early childhood speech delay, including knowledge of signs, causal factors, and intervention strategies used in the home environment. A qualitative approach with a case study method was chosen as the approach and type of this research. The research subjects consisted of eight parents in RT 22 Kebun Bunga Village, East Banjarmasin, South Kalimantan, who have children aged 3 to 6 years. Data were collected through semi-structured interviews and participatory observation, then analyzed using data reduction, data presentation, and conclusion drawing stages. The results indicates that most parents only understood speech delay in general without recognizing specific language development indicators. The known causative factors are limited to the use of gadgets and lack of verbal interaction, while innate factors such as medical or neurological conditions are less understood. Interventions are still simple and unsystematic, such as inviting children to continue interacting and sending children to PAUD institutions. This finding indicates the need to increase parental literacy related to language development.